2011
DOI: 10.1111/j.1467-789x.2010.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of childhood obesity prevention interventions targeting Hispanic children: lessons learned from the previous decade

Abstract: SummaryHispanic children suffer from the highest overall rates of prevalence for overweight and obesity in the US. In the last decade some interventions for prevention of childhood obesity have been developed and tailored to target this subgroup. The purpose of this review is to systematically analyze and summarize findings for health education and promotion interventions aimed at the prevention of childhood overweight and obesity among primarily Hispanic children. A systematic review of PubMed, CINAHL, and ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 23 publications
(24 reference statements)
5
77
0
Order By: Relevance
“…Previous research has documented that Latino parents welcome suggestions regarding how to make traditional Latino foods healthier, suchassubstitutingwhole-wheatforflour tortillas, water with lemon for sugary beverages, and fish for red meat, and including more vegetables in meals 28 ; and culturally tailored obesity interventions have been shown to effectively reduce BMI and improve target health behaviors among Latino-American and MexicanAmerican children. [29][30][31] Also noteworthy, although not significant, was the higher frequency of communication regarding traditional foods among LI versus LC groups. It is possible that LI underscored cultural differences, and perhaps the need to address culturally relevant dietary plans.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has documented that Latino parents welcome suggestions regarding how to make traditional Latino foods healthier, suchassubstitutingwhole-wheatforflour tortillas, water with lemon for sugary beverages, and fish for red meat, and including more vegetables in meals 28 ; and culturally tailored obesity interventions have been shown to effectively reduce BMI and improve target health behaviors among Latino-American and MexicanAmerican children. [29][30][31] Also noteworthy, although not significant, was the higher frequency of communication regarding traditional foods among LI versus LC groups. It is possible that LI underscored cultural differences, and perhaps the need to address culturally relevant dietary plans.…”
Section: Discussionmentioning
confidence: 98%
“…Childhood obesity disproportionately affects Latino children and adolescents in the US. 3,4 Latino boys, aged 2-19 years, were found to be significantly more likely to be obese than non-Latino white boys. Obesity prevalence was higher among Hispanic youth (22.4%) and non-Hispanic black youth (20.2%), compared with non-Hispanic white youth (14.1%) in 2012-2014.…”
mentioning
confidence: 94%
“…Studies specifically addressing the components of school-based parent education programs to include curriculum design (Evan et al, 2011;Gable & Lutz, 2000;Schwartz and Puhl, 2003;Wechsler, McKenna, Lee & Dietz, 2004) and cultural considerations (Ayala, Baquero, Arredondo, Campbell, Larios, & Elder, 2007;Branscum & Sharma, 2011;LCHC, 2006) are examined in the following section.…”
Section: School-based Parent Interventionsmentioning
confidence: 99%
“…It was important for study participants that families support each other for healthful eating and eat meals together. In another study, Branscum and Sharma (2011) conducted a systematic analysis of nine Hispanic childhood obesity prevention programs. They concluded that interventions were successful when incorporating a parental component, sessions were longer in length, and when delivered by staff who were dedicated to and familiar with the Hispanic culture.…”
Section: School-based Parent Interventionsmentioning
confidence: 99%